Oral cavity cancer management guidelines for low‐resource regions. Issue 3 (21st January 2019) - Cervenka, Brian; Pipkorn, Patrik; Fagan, Johannes; Zafereo, Mark; Aswani, Joyce; Macharia, Chege; Kundiona, Innocent; Mashamba, Victor; Zender, Chad; Moore, Michael
Abstract: Background: The diagnosis and management of oral cavity cancer has been well described in developed countries, however, in regions with fewer medical resources, alternative methods may need to be used. We outline an approach to evaluation and treatment of oral cavity cancer in low‐resource areas. Methods: Reviews of the Cochrane and Pubmed databases were performed and literature compiled. Expert opinions from the American and African Head and Neck Societies were also provided. Results: Treatment guidelines for managing oral cavity cancer in low‐resource regions are outlined and the level of supporting evidence is defined. Discussion: Successful treatment typically involves the use of upfront surgical resection of the primary lesion and any involved or at‐risk cervical lymph node basins, with adjuvant therapy based on the final pathology findings. In situations where services such as adjuvant therapy and/or appropriate reconstruction are not available, alternative approaches to treatment may be needed.